Dos e Re spons e Biot ip Rumput Be lulang (El eus ine indi ca(L. ) Gae r tn. ) Resisten-Parakuat Terhadap Parakuat, Diuron, Dan Ametrin - Dani Hambali; Edison Purba; Emmy Harso Kardhinata (Jurnal Agroekoteknologi, 2015)
Goosegrass is one of weeds that had negative effect on crops which is commonly found in oil palmplantation. In the past few years, the existence of this weed in Adolina Estate, PTPN IV has beenreported that population was difficult to control with paraquat and glyphosate. This research aims todetermine the dose response of the multiple herbicide resistance in Eleusine indica population toparaquat, diuron, and ametryn. The levels of paraquat applied were 0, 50, 100, 200, 400, 800, 1600g a.i. ha-1; diuron at 0, 187,5, 375, 750, 1500, 3000, 6000 g a.i. ha-1, and ametryn at 0, 62,5, 125,250, 500, 1000, 2000 g a.i. ha-1. The treatments were arranged in randomized block design (RBD)and each treatments was made in three replication.The results showed that the multiple resistantpopulationEluesine indica from area of Adolina Estate, PTPN IV was reconfirmed resistant toparaquat but, diuron and ametryn controlled satisfactorily this population.Keywords : Paraquat, Diuron, Ametryn, Goosegrass, Resistance